P. Allsworlh-Jones. Jhe Szeletian and the Transition from Middle to Upper Paiaeolithie in Central Europe - Демиденко, Ю.Е.; Кулаковська, Л.В. (Археологія, 1993)
Рецензія на книгу: Allsworth-Jones Р. The Szeletian and the Transition from Middle to Upper Palaeolithic ir Central Europe.— Oxford, 1986.— 412 p.